2012
DOI: 10.1194/jlr.m026674
|View full text |Cite
|
Sign up to set email alerts
|

Nascent high density lipoproteins formed by ABCA1 resemble lipid rafts and are structurally organized by three apoA-I monomers

Abstract: In humans, the plasma concentration of HDLs has been repeatedly shown to be inversely correlated with the risk of developing coronary heart disease ( 1, 2 ). The concentrations of plasma HDL has been shown to be largely dependent on hepatic ATP-binding cassette transporter A1 (ABCA1) ( 3-5 ), which transports and promotes the effl ux of glycerophosphocholine (PC), free cholesterol (FC), and sphingomyelin (SM) to wild-type apolipoprotein A-I (apoA-I), resulting in the formation of nascent HDLs (nHDLs). Function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
147
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(159 citation statements)
references
References 98 publications
8
147
1
Order By: Relevance
“…Whereas the adventitial lymphatic vessels are now accepted as important modulators of cholesterol transport between the atherosclerotic lesion and the bloodstream, the apoA‐I (apolipoprotein A‐I) has been identified as a key regulator of cellular cholesterol efflux via the ABCA1 receptor present at the cell surface 29, 30. ApoA‐I is the main protein constituent of plasma high‐density lipoprotein (HDL) and participates in its highly heterogeneous properties 31, 32.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the adventitial lymphatic vessels are now accepted as important modulators of cholesterol transport between the atherosclerotic lesion and the bloodstream, the apoA‐I (apolipoprotein A‐I) has been identified as a key regulator of cellular cholesterol efflux via the ABCA1 receptor present at the cell surface 29, 30. ApoA‐I is the main protein constituent of plasma high‐density lipoprotein (HDL) and participates in its highly heterogeneous properties 31, 32.…”
Section: Introductionmentioning
confidence: 99%
“…All helixto-helix interactions present in the double belt between two molecules of apoA-I in a disc ( Fig. 6C ) ( [112][113][114][115][116]. There are variations in the distributions of classes of PL molecules across the HDL species, and larger particles are relatively FC-enriched.…”
Section: Apoa-i Organization In Spherical Hdlmentioning
confidence: 99%
“…Depending on the detergents employed, ABCA1 has been reported to reside either in detergent-soluble membrane or partly in DRM; ABCA1 was recovered in detergent-soluble membrane when TX100 was used ( 35 ), while a fraction of this protein was recovered in DRM prepared using Lubrol WX ( 36 ). A recent work showed that lipid composition of nascent HDL particles generated by the ABCA1/apoA-I system is similar to that of lipid rafts ( 53 ). Heterogeneity of lipid raft domains has been reported; the protein and lipid contents/ compositions of DRM vary greatly depending on the detergents used ( 44,54 ).…”
Section: Abca1 Is Present In the Cholesterol-rich Membrane Domainmentioning
confidence: 99%